Solvent-regulable interfacial groups enable on-demand superhydrophobic/superhydrophilic silica aerogels - Lixiao Chen; Lishan Li; Xuetong Zhang (Nature Communications)
Abstract Silica aerogel, as the earliest synthetic and commercially available one among all known aerogels, holds significant value in fields including thermal and acoustic insulation, optics, catalysis, sorption, etc. However, throughout its nearly century-long history, the influence of solvent used during synthesis on the properties of silica aerogels has been neglected, resulting in inaccurate and ambiguous performance evaluation. Herein, we have uncovered and systematically investigated the solvent-regulable interfacial groups that enable on-demand superhydrophobicity/superhydrophilicity of silica aerogels. During either sol-gel transition or solvent exchange process both required for aerogel synthesis, the alteration of solvent either from water to ethanol or vice versa leads to silica interfacial groups switch from superhydrophilic Si-OH to superhydrophobic Si-OEt or reversely due to reversible esterification, thus enabling on-demand superhydrophobic/superhydrophilic silica aerogels. It is worth noting that on-demand solvent-regulated hydrophilicity/hydrophobicity holds true regardless of used silica precursors (the mixture of trimethoxymethylsilane (MTMS)/tetramethoxysilane (TMOS), MTMS/tetraethyl orthosilicate (TEOS), or sodium methicosilicate (SMS)/TMOS), thereby indicating its universality, which wakes up considerable attention for producers involved in silica aerogels. Additionally, the discovery also provides a green, economical, and efficient way to achieve silica aerogels with on-demand hydrophilic/hydrophobic performance for specific sorption, etc.